Forest machinery fires : trends in New Zealand forest harvesting sector - Visser, Rien (Array, 2021)
Fires in forest machines are typically catastrophic in terms of machine destruction and can develop rapidly to be a risk to the machine operator. They are an issue worldwide and there can be larger consequences such as starting a major forest fire. This paper describes trends in machine fire occurrences in the New Zealand forest harvesting sector. A total of 224 machinery fire incidents were recorded over an 8 year period from 2007 to 2014. Trends in forest machinery fires in the sector were identified and summarized. Late morning (10 am-noon) and mid-afternoon (2–4 pm) showed the highest incidence of machine fire, corresponding to periods with the highest level of work. Excluding the main holiday months, there was a correlation of machine fires to average monthly temperature. Summary statistics on causes of fire ignition showed that 40% were attributed to electrical and hydraulic faults; however, some remain unidentified as the fires commenced after work was completed. A short survey of industry managers was carried out to ascertain machine fire perceptions. 67% agreed that machine fire was an issue, and only 33% thought the current industry procedures were sufficient to mitigate them. The report concludes with proactive measures to reduce the incidence of forest machine fire risk.